Regional wage disparities in post-apartheid South Africa: spatial patterns, convergence dynamics, and causes - Mudiriza, Gibson (School of Economics, 2018)
This thesis examines the spatial patterns, convergence dynamics, and causes of regional wage disparities in post-apartheid South Africa. The analysis is conducted using a unique dataset for 354 regions constructed from the 1996, 2001 and 2011 population censuses. The thesis comprises of six chapters including the introduction and conclusion. The general introduction is followed by Chapter two that presents a theoretical and empirical review of the causes of regional wage disparities. Emphasis is placed on theoretical insights derived from the new economic geography theory. The subsequent 3 chapters comprise the empirical analysis. Chapter three applies exploratory spatial data analysis techniques to the 1996, 2001 and 2011 population censuses data and examines the spatial patterns that characterise the distribution of wages across regions in South Africa. An objective is to assess the consistency of these patterns with predictions from alternative theories. The results point to significant disparities in the distribution of wages across regions in South Africa that are greater than regional wage disparities in other countries. These disparities are characterised by positive and negative spatial autocorrelation between regions suggesting the coexistence of new economic geography forces (positive autocorrelation) and alternative economic theory (negative autocorrelation) features. These findings provide important context and input into the subsequent empirical chapters of the thesis. Chapter four examines the convergence dynamics of wages across regions in post-apartheid South Africa. The aim of the chapter is to assess the extent to which wages have converged or diverged across regions in South Africa over the period 1996 – 2011. The convergence dynamics are analysed using a range of complementary measures, namely, the kernel density estimator and indicators of α - convergence and β - convergence. These measures consistently reveal evidence of regional wage divergence between 1996 and 2001, but strong and robust evidence of regional wage convergence from 2001 to 2011. During the period 2001 – 2011, the unconditional β- convergence is estimated at 3.7% per year, suggesting that it could take about 19 years to reduce the gap in wages between rich and poor regions by half. However, conditional β- convergence, after controlling for initial human capital, local unemployment, market potential, industrial stucture and homeland status, is much higher, at 13% per year. This implies that it could have taken about 5 years to reduce the wage gap between rich and poor regions by half, if differences in regional specific factors had been eliminated between 2001 and 2011. The results suggest that regional specific factors, some of which can be influenced by policy, constrain regional wage convergence in South Africa. The fifth Chapter empirically tests whether the prediction of the Helpman-Hanson wage equation derived from the new economic geography theory is consistent with observed regional wage disparities in South Africa. The chapter extends the Helpman-Hanson model to include other potential explanatory factors concerning regional wages. The results suggest that regional wage disparities in South Africa are well explained by new economic geography forces such as access to markets, but only after controlling for regional specific factors such as human capital, mineral resource endowments, local climatic conditions, local unemployment, and homeland status. The findings of this study imply that new economic geography theory alone is not sufficient to explain regional wage disparities in South Africa. Its proper application hinges on the incorporation of other regional specific factors. This finding is consistent with an emerging economy that is characterised by moderate industrial and transport sectors, on the one hand, and a strong primary sector driven by natural resource exploitation, on the other hand. Overall, the thesis shows that, while regional wage disparities are converging over time in South Africa, they remain high compared to other countries. Convergence is very slow and is influenced by regional specific factors such as human capital, access to markets, mineral resource endowments, local climatic conditions, local unemployment and homeland status. Accordingly, complementary policies promoting human capital accumulation, access to markets, and development of former homeland areas, and improving labour market outcomes will substantially enhance wage convergence. Nevertheless, even with these policies, regional wage disparities will remain a feature of the South African economy as these are in part driven by economic forces associated with new economic geography. The thesis thus highlights how differences in access to markets and regional factor endowments exacerbate and constrain regional wage disparities in South Africa.